Prospects for new drugs to treat binge-eating disorder: Insights from psychopathology and neuropharmacology. (June 2022) - Heal, David J; Smith, Sharon L
Background: Binge-eating disorder (BED) is a common psychiatric condition with adverse psychological and metabolic consequences. Lisdexamfetamine (LDX) is the only approved BED drug treatment. New drugs to treat BED are urgently needed. Methods: A comprehensive review of published psychopathological, pharmacological and clinical findings. Results: The evidence supports the hypothesis that BED is an impulse control disorder with similarities to ADHD, including responsiveness to catecholaminergic drugs, for example LDX and dasotraline. The target product profile (TPP) of the ideal BED drug combines treating the psychopathological drivers of the disorder with an independent weight-loss effect. Drugs with proven efficacy in BED have a common pharmacology; they potentiate central noradrenergic and dopaminergic neurotransmission. Because of the overlap between pharmacotherapy in attention deficit hyperactivity disorder (ADHD) and BED, drug-candidates from diverse pharmacological classes, which have already failed in ADHD would also be predicted to fail if tested in BED. The failure in BED trials of drugs with diverse pharmacological mechanisms indicates many possible avenues for drug discovery can probably be discounted. Conclusions: (1) The efficacy of drugs for BED is dependent on reducing its core psychopathologies of impulsivity, compulsivity and perseveration and by increasing cognitive control of eating. (2) The analysis revealed a large number of pharmacological mechanisms are unlikely to be productive in the search for effective new BED drugs. (3) The most promising areas for new treatments for BED are drugs, which augment noradrenergic and dopaminergic neurotransmission and/or those which are effective in ADHD.